Marketing strategies in small firms: how far do small medium industries understand the marketing concept? / Shafiza Ab Sani - Ab Sani, Shafiza (Faculty of Business and Management, 2004)
In recent years, the growth of small firms and their importance to the nation's economies has been accompanied by a significant increase in interest in the nature of marketing practices. The mass consumer markets have become fragmented and call for flexible and adaptable marketing approaches (Baker 1995) especially to the smaller organisations (Carson et al 1995).